The Urgency of Standardizing National Disaster Parameters: A Critical Study of the Mechanism for Determining the Scale of Disasters by the Government Post-Disaster in Sumatra - Cynthia Hadita (Lembaga Riset Mutiara Akbar, 2025)
Indonesia lacks standardized and measurable parameters for determining national disaster status, as reflected in the government’s response to disasters in Sumatra (Aceh, North Sumatra, and West Sumatra). The absence of clear indicators—such as casualty thresholds, infrastructure damage, regional response capacity, socio-economic impacts, and the urgency of central intervention—has led to inconsistent status determinations and legal uncertainty. This study examines the urgency of standardizing national disaster parameters through a critical analysis of the disaster scale determination mechanism under Law No. 24 of 2007 on Disaster Management and its implementing regulations. Using a socio-legal approach, the study analyzes gaps between legal norms and empirical practices following the late-2026 Sumatra disaster and identifies weaknesses in coordination among the National Disaster Management Agency (BNPB), regional governments, and related ministries. The findings indicate that disaster status determination remains highly subjective and politically influenced due to the absence of standardized benchmarks. Therefore, this study recommends reformulating national disaster parameters by integrating impact indicators, regional capacity assessment, and rapid assessment mechanisms to strengthen legal certainty and disaster governance.